Doctors treating family members: A qualitative study among primary care practitioners in a teaching hospital in Malaysia - Nik-Sherina, H.; Ng, C.J. (2006)
Aim: To explore primary care practitionersâ experiences and feelings about treating their own family members. Methods: A qualitative study was carried out using focus group discussions. Five sessions were held among 22 primary care practitioners (five academic staff members and 17 medical officers). Results: Most participants treated their family members, especially their immediate families. They considered factors such as duration and severity of illness before seeking consultation with other doctors. Some participants felt satisfied knowing that they were able to treat their own families. However, most felt burdened and uncomfortable in doing so, mainly due to the fear of error in diagnosis and management. They were concerned that strong emotions may make them lose objectivity. Many were aware that negative outcomes resulting from their treatment may affect future relationships. Conclusions: While some doctors were comfortable about treating their own families, some faced significant conflict in doing so. Their decisions depended on the interplay of factors including the doctor, the family member and the relationship they share. A doctor needs to consider the potential conflict that may arise when carrying out oneâs professional role and at the same time being a concerned family member.